Polythene Mulch and Irrigation for Mitigation of Salinity Effects on Maize (Zea mays L.) (The Agriculturists, 2017)
A pot experiment was conducted at the net house of Patuakhali Science and Technology University during rabi season 2014-15 to estimate the contribution of polythene mulch and irrigation on reducing of salinity effect on maize (Zea  mays L.). The experiment was laid out in a three factors randomized complete block design with three replications. The factors were salinity (two levels: without and 5 dS/m salinity), mulch (two levels: without and with polythene mulch) and irrigation (three levels: 125, 250 and 500 ml water/irrigation). BARI hybrid maize-7 was the test crop. Every pot received the same amount of fertilizer nutrients. Crops were harvested at tassel initiation stage. Mulch increased soil temperature by 2 to 4.5°C (with average of 3.1°C) over without mulch. In without mulch condition, salinity reduced shoot fresh and dry, and root fresh and dry weight by 28.3, 10.3, 39.4 and 30.6%, respectively. In with mulch condition, however, these reductions were 1.0, 7.2, 12.3 and 12.1 %, respectively. Polythene mulch reduced salinity induced reduction of the above parameters by 96.5, 30.1, 68.8 and 60.5 %, respectively. Under 125, 250 and 500 ml water/irrigation treatment, salinity reduced shoot fresh weight by 14.2, 19.3 and 6.7 %, respectively; shoot dry weight by 15.4, 6.6 and 5.0 %, respectively; and root fresh weight by 27.5, 20 and 11.6 %, respectively. Thus, the effect of salinity in maize was gradually decreased with the increasing amounts of irrigation water. Soil salinity reduced phosphorus and increased sulphur content in maize plants.The Agriculturists 2016; 14(2) 01-13